Handbook of Grammatical Evolution 2018
DOI: 10.1007/978-3-319-78717-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Grammatical Evolution: Grammar Design

Abstract: A frequently overlooked consideration when using Grammatical Evolution (GE) is grammar design. This is because there is an infinite number of grammars that can specify the same syntax. There are, however, certain aspects of grammar design that greatly affect the speed of convergence and quality of solutions generated with GE. In this chapter, general guidelines for grammar design are presented. These are domain-independent, and can be used when applying GE to any problem. An extensive analysis of their effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The study was inconclusive, as no statistically significant differences were found between using the original grammar and using the corresponding simplified grammar. More consistent results regarding the relation between grammar structure and search effectiveness have been found recently by Nicolau and Agapitos [12] in the context of GE with linear genome representation. The cited work mostly focused on symbolic regression problems and considered several grammar design aspects, including grammar balancing, type of notation, and symbol biases.…”
Section: Grammatical Evolutionsupporting
confidence: 84%
See 3 more Smart Citations
“…The study was inconclusive, as no statistically significant differences were found between using the original grammar and using the corresponding simplified grammar. More consistent results regarding the relation between grammar structure and search effectiveness have been found recently by Nicolau and Agapitos [12] in the context of GE with linear genome representation. The cited work mostly focused on symbolic regression problems and considered several grammar design aspects, including grammar balancing, type of notation, and symbol biases.…”
Section: Grammatical Evolutionsupporting
confidence: 84%
“…The key idea is that if a better candidate solution has a higher probability of being generated, then the entire evolutionary search can reach the optimum faster. In fact, it has already been shown experimentally that the quality of the initial population [15] and the biases in the grammar [12] can greatly influence the effectiveness and efficiency of the search. However, we remark that degenerate cases exist: for example, with trap functions [47], increasing the average fitness of the generated candidate solutions might be counterproductive because we might favor the convergence toward local optima, rather than the global optimum.…”
Section: B Quality Of the Grammar For A Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…e level of abstraction is also important: lower levels of abstraction usually have more elements and possible combinations. As for the grammar design, good practices can be found in the work of Nicolau and Agapitos [40].…”
Section: Limitationsmentioning
confidence: 99%